La mujer marroquí como protagonista del proyecto migratorio: aspectos victimológicos = The moroccan woman as protagonist of the migration project : victimological aspects - Orbegozo Oronoz, Izaskun (Revista de victimología, 2023)
The migratory flow from Islamic countries, specifically from Morocco, has women as protagonists, unlike what used to happen in the past when they joined the husband’s migratory project. However, when they arrive in the host country, having sometimes been exposed to situations of trafficking for sexual exploitation and prostitution, the latter denies them a series of recognitions of de facto situations legally constituted in their country of origin, returning to the situation of victimization, helplessness and inequality previously experienced in their own country.